Mathematical Modeling of Rocks Plasma Disintegration Process at Borehole Reaming - Potapchuk, Iryna Yu.; Zhevzhyk, Oleksandr V.; Kholiavchenko, Leonid; Pertsevyi, Vitalii; Bosyi, Dmytro O.; Drubetskaya, Tanya; Potapchuk, Anna (IOP Publishing Ltd, 2023)
ENG: The mathematical model of thermal disintegration of rocks during the reaming of boreholes, which takes into account the compatibility of the thermogas dynamic problem for a high-temperature heat transfer agent and the thermal problem for the rock heated by this heat transfer agent, has been developed. The mathematical model is based on the laws of conservation of mass, quantity of motion and energy and takes into account the dependences for determining the thermal stresses and the temperature of brittle fracture of rocks. As a result of solving the equations of the mathematical model, the temperature distribution in the rock mass (magnetite quartzite) during heating in the process of borehole plasma reaming and productivity of the borehole plasma reaming process are obtained. Calculated and experimentally determined productivity of the process of plasma reaming of the borehole were compared.
O. Zhevzhyk: ORCID 0000-0002-8938-9301, V. Pertsevyi: ORCID 0000-0002-4322-7921, I. Potapchuk: ORCID 0000-0002-5985-1040, D. Bosyi: ORCID 0000-0003-1818-2490, T. Drubetskaya: ORCID 0000-0002-8580-9719
Keywords: mathematical model; rocks plasma; borehole reaming; laws of conservation of mass; plasma reaming of the borehole; КІСЕ